Belgian heart disease prevention project: comparison of self-reported smoking behaviour with serum thiocyanate concentrations. - Kornitzer, M (1983)
At the end of a multifactorial cardiovascular preventive trial serum thiocyanate was measured in random samples of 1035 cases and 1087 controls. A cut-off point 0.45 mg/dl (77.6/mumol/l) gave a sensitivity of 82.1% among the cigarette smokers in the control group and a specificity of 91.0% among the non-smokers. When the intervention and control groups are compared in terms of self-reported smoking behaviour non-significant differences in mean thiocyanate concentration are observed for those who never smoked, ex-cigarette smokers, actual cigarette smokers, and in four different cigarette smoking categories. Our results fail to confirm the reported pessimistic views concerning the validity of self-reported smoking behaviour in subjects taking part in intervention trials.